ASSOCIATION BETWEEN ISTHMIC LOCATION AND INVASIVE FEATURES AND CERVICAL LYMPH NODE METASTASIS IN PATIENTS WITH SOLITARY PAPILLARY THYROID CARCINOMA (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the clinical and histopathological characteristics of solitary papillary thyroid carcinoma and evaluate the association between isthmic location and features of tumor invasion as well as cervical lymph node metastasis.Methods: A retrospective cohort study was conducted on 261 patients with solitary papillary thyroid carcinoma who underwent surgery at Thanh Hoa Oncological Hospital between April 2023 and May 2026. Clinical and histopathological data were collected and analyzed for 38 patients with isthmic tumors and 223 patients with lobar tumors.Results: The rate of capsular invasion was significantly higher in the isthmic group than in the lobar group (44.7% vs. 18.9%, p = 0.0001). After adjustment for age, sex, and tumor size, isthmic location remained independently associated with capsular invasion (adjusted OR = 3.54; 95% CI: 1.70-7.38; p = 0.001). The rate of central lymph node metastasis was 52.6% (20/38 cases) in the isthmic group compared to 48.2% (96/199 cases) in the lobar group (p = 0.620). However, high-volume central lymph node metastasis (> 5 metastatic central lymph nodes) was observed in 18.4% of patients in the isthmic group compared with 6.0% in the lobar group (p = 0.018).Conclusions: In solitary papillary thyroid carcinoma, isthmic location is independently associated with capsular invasion and correlates with a high burden (> 5 metastatic lympho nodes) of central lymph node metastasis.
Keywords: Papillary thyroid carcinoma, isthmus thyroid cancer, cervical lymph node metastasis.